(3)^ 7.5 ÷ (27)^1.5 x (9)^2 = 3? ⇒(3)^7.5 ÷ {(3)^(3 x 1.5)} x {(3)^(2 x 2)} = 3 ? ⇒ 3^(7.5 – 4.5 + 4) = 3? ⇒ 3^7 = 3? ⇒ ? = 7 Reply
(3)^ 7.5 ÷ (27)^1.5 x (9)^2 = 3? ⇒(3)^7.5 ÷ {(3)^(3 x 1.5)} x {(3)^(2 x 2)} = 3 ? ⇒ 3^(7.5 – 4.5 + 4) = 3? ⇒ 3^7 = 3? ⇒ ? = 7 Reply
( c ) 7
Comments on previous answer. Your answer is correct but can
u tell me how to solve it?????
(3)^ 7.5 ÷ (27)^1.5 x (9)^2 = 3?
⇒(3)^7.5 ÷ {(3)^(3 x 1.5)} x {(3)^(2 x 2)} = 3 ?
⇒ 3^(7.5 – 4.5 + 4) = 3?
⇒ 3^7 = 3?
⇒ ? = 7
(3)^ 7.5 ÷ (27)^1.5 x (9)^2 = 3?
⇒(3)^7.5 ÷ {(3)^(3 x 1.5)} x {(3)^(2 x 2)} = 3 ?
⇒ 3^(7.5 – 4.5 + 4) = 3?
⇒ 3^7 = 3?
⇒ ? = 7